Estudo comparativo de indicadores de saúde bucal em município do estado de São Paulo - Magri, Laís Valencise; Aciole, Geovani Gurgel; Salomão, Fernanda Gonçalves Dutra; Tagliaferro, Elaine Pereira Da Silva; Ribeiro, Lucas Gaspar (Centro Brasileiro de Estudos de Saúde, 2016)
To compare four oral health indicators (Income, Attrition, Modified Prevention Emphasis, Restoration/Extraction) and the 1st Consultation/Urgency Relationship in 15 Family Health Units and 11 Basic Health Units, in an interior city of São Paulo State, 2008-2011. The data were collected from SIA-SUS and the indicators compared through historical series using the non-parametric test (Mann Whitney) and descriptive statistics. Although there is a strengthening process of the Family Health Strategy, the care model represented by the Basic Health Units still proves more effective in some aspects of oral health in public service.

Comparar indicadores de saúde bucal (Rendimento, Atrição, Ênfase em Prevenção Modificado, Relação Restauração/Extração) e Relação 1ª Consulta/Urgência entre 15 Unidades de Saúde da Família e 11 Unidades Básicas de Saúde de município do interior paulista, de 2008 a 2011. Os dados foram coletados a partir do Sistema de Informações Ambulatoriais do SUS (SIA-SUS) e comparados os modelos de atenção por meio de série histórica, teste não paramétrico (Mann-Whitney) e estatística descritiva. Embora haja o processo de fortalecimento da Estratégia Saúde da Família o modelo assistencial representado pelas Unidades Básica de Saúde se mostra mais efetivo em alguns aspectos da saúde bucal no serviço público.
Comparative study of oral health indicators in primary care of a São Paulo State's city
Keywords: Community dentistry; Health status indicators; Information systems; Dental health services; Primary Health Care; Odontologia comunitária; Indicadores básicos de saúde; Sistemas de informação; Serviços de saúde bucal; Atenção Primária à Saúde